COAL MINING SECTOR CONTRIBUTION TO ENVIRONMENTAL CONDITIONS AND HUMAN DEVELOPMENT INDEX IN EAST KALIMANTAN PROVINCE - Afkarina, Kunny Izza Indah; Wardana, Sindhung; Damayanti, Poerborini (UI Scholars Hub, 2019)
Coal mining has been one of the issues that led to pros and cons in Indonesia. Research shows that mining activities are one of the factors that affect people’s incomes and local and national economic development. However, mining is a lucrative activity that leads to construction booms that attract population growth and lead to deforestation, thus affecting the environmental conditions of a region. The coal mining industry of Indonesian province of East Kalimantan, on the island of Borneo, provides most of the economic base needed to build the infrastructure and provide energy of the country. Kalimantan Province accounts for approximately 90 % of the entire country’s coal production. East Kalimantan, with its mining operations mainly in the district of Kutai and its expanded territory, is a major coal-producing region of the country. This article will examine how coal mining sector contributes to environmental conditions and Human Development Index (HDI) in the province of East Kalimantan. This research was conducted using a combination of scientific methods, including literature, spatial analysis using geographic information system (GIS) technology, and quantitative data analysis. From the analysis of the spatial issuance of coal mining permit in East Kalimantan, the coal mining sector has a direct impact on regional revenue and contributes indirectly to the HDI in the province of East Kalimantan. However, it turns out that the planning and management of natural resources field exploitation business licenses are not performed systematically. As a result, many problems arise, such as disputes over control and ownership of land (agrarian conflicts), damage to the landscape, deforestation, environmental pollution, and public health problems. Thus, anticipatory measures are needed by the government so that the economy of East Kalimantan Province remained stable and sustainable.